A women-only university in the XXI century - García García, Victoria (2013)
In the present interview, Ph.D. Victoria García García talks about the evolution of UNIFEUniversity, as University of Women in Peru, throughout 50 years of institutional life.Currently, Ph.D. García is the Academic Deputy Vice – Chancellor of UNIFE University. Shestudied Psychology in one of the first proms of the university. She has 37 years of trajectory asuniversity teacher. In 2005 she receives the Distinguished Teaching University Award and in 2009she received the National Psychology Award, both prizes awarded by the Peruvian Collegue ofPsychologist.To make clear the treated subject, the interview was raised in 12 questions.